Investigation of Used Engine Oil Lubricating Performance Through Oil Analysis and Friction and Wear Measurements - András Lajos Nagy; Jan Christopher Knaup; Ibolya Zsoldos (Acta Technica Jaurinensis, 2019)
Engine oil degradation during long-term engine operation is a well-researched topic, however, the effect of biofuels and synthetic compounds is not fully understood. In order to characterise novel fuel related phenomena in an engine a basis of studies should be established with state-of-the-art engines and conventional fuels and lubricants. This study aims at describing the behaviour of used engine oils throughout their service life based on friction and wear measurements with oil samples from three identical light-duty direct injection supercharged diesel engines. Oil samples were taken from each engine every 50 hours between oil changes to determine physical properties and chemical composition. Friction and wear measurements were conducted on a high-frequency reciprocating rig. The results show strong correlation between oil service life and boron content, as well as acid number and base number. A similar correlation between coefficient of friction with used samples and boron content as well as soot content was observed. A simple model based on a polynomial fitting function was proposed to predict friction and wear from boron content, total acid number and total base number.